Supercritical Water Oxidation of 3-Methylpyridine with Propylene Glycol - Kareem Hadi Al-Kaabi, Falah; Al-Duri, Bushra; Kings, Iain (Asian Journal of Chemistry, 2021)
The destruction of 3-methylpyridine by supercritical water oxidation (SCWO) using propylene glycol (PG) and isopropyl alcohol (IPA) as co-fuels in a plug flow reactor was carried out. Hydrogen peroxide was the oxygen source. All the experiments were carried out at 25 MPa and a range of temperatures from 425-525 ºC. The residence times range from 6 s to 14 s. Results were presented in terms of total organic carbon (TOC) as a function of time with various process parameters. The findings support the positive effect that propylene glycol has on the destruction of 3-methylpyridine, where TOC removal is ≥ 97.5% at 525 ºC and 14 s. The maximum TOC removal efficiency is 93% at 425 ºC, 14 s, and the [propylene glycol]/[3-methylpyridine]o ratio of 3. The removal efficiency of nitrogen in the presence of propylene glycol reaches 89% at 525 ºC and 10 s. The oxidant ratio also has a positive effect on the removal of TOC in the three systems. Addition of propylene glycol causes a significant development in the ratio at 425 ºC, more so than when isopropyl alcohol was added. This is due to two hydroxyl groups in propylene glycol oxidation that enhance the reaction by generating various free radicals.